Comparison of Protective Effects of Melatonin and Amifostine on Radiation-Induced Renal Oxidative Stress in Rats - CAKINA, S.; GULYASAR, T.; ÖZEN, A.; PARLAR, S.; CUKUR, Z.; KURKCU, N.; UZAL, C.; SENER, S. (Journal of the Hellenic Veterinary Medical Society, 2020)
In this study, we aimed to compare the protective effects of melatonin and amifostine on radiation-induced oxidative stress. Fifty female Wistar rats (3-4 months old, weighing 200±25 g) were divided into five groups (with ten rats each) and treated as follows: control (Cont), radiotherapy alone (RT), radiotherapy + amifostine (RT+AMI), radiotherapy + melatonin (RT+MEL), radiotherapy + amifostine + melatonin (RT+AMI+MEL). Rats were irradiated individually with a single dose of 8 Gy and amifostine (200 mg/kg) and melatonin (10 mg/kg) was administered to rats 30 minutes before irradiation. At the end of this follow-up period (72 hours) the rats were sacrificed. Spectrophotometric Analysis has been performed to kidney tissue samples. As a result of statistical comparison between groups after RT, total antioxidant capacity (TAC) decreased, total oxidant status (TOS) and oxidative stress index (OSI) increased, although the statistically significant change was only for OSI (p = 0.030). Addition of AMI or MEL to RT increased TAC and OSI significantly (p = 0.000), but there was no additive effect for TAC and OSI when both drugs were given together (p = 1.000, p = 0.172, respectively). In terms of TOS, statistically significant increasing was only for AMI (p = 0.000). There was protective effect when both drugs were given together against on Radiation-Induced Renal Oxidative Stress.